Critical Narrative Analysis in Psychology - Emerson, Peter. author. aut Link
VII, 170 p.
Keywords: This book presents an approach to narrative analysis from a critical social perspective. It describes the background to discursive and narrative approaches and then takes the reader through a variety of analysis at different 'levels'. These focus on narrative texts from a boy labelled as 'sexually abusive', analyzed seqentially from micro- to more global levels. Through this extended example, the book demonstrates the power of narrative analytic procedures and the different effects produced by different levels of analysis.